2004
DOI: 10.1111/j.1472-765x.2003.01461.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of heat stable protease of Klebsiella oxytoca isolated from raw milk

Abstract: Aims: The aim of this study was to identify and characterize heat stable proteinases of psychrotrophic proteolytic bacteria isolated from raw milk. Methods and Results: A strain of Klebsiella oxytoca producing a high proteolytic activity when cultured on milk was isolated. Maximum proteolytic activity was observed at the stationary phase during growth on milk or caseinpeptone broth. The bacterium demonstrated the capability to grow at 7°C, classified as psychrotrophic. The crude enzyme showed optimum activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 13 publications
2
16
0
6
Order By: Relevance
“…Microbial proteases from psychrotrophic bacteria have been related to the coagulation or gelation of milk proteins, but few studies have demonstrated such defects by direct addition of proteases to milk samples (Datta and Deeth ; Tondo et al . ). UHT milk produced with low‐quality milk (psychrotrophic counts 4.7 log cfu/mL, photolytic activity 0.71 U/mL) showed an increase of 74.7% in soluble N values after 180 days versus 33.8% observed for high quality milk (3.2 log cfu/mL, 0.42 U/mL).…”
Section: Resultsmentioning
confidence: 97%
“…Microbial proteases from psychrotrophic bacteria have been related to the coagulation or gelation of milk proteins, but few studies have demonstrated such defects by direct addition of proteases to milk samples (Datta and Deeth ; Tondo et al . ). UHT milk produced with low‐quality milk (psychrotrophic counts 4.7 log cfu/mL, photolytic activity 0.71 U/mL) showed an increase of 74.7% in soluble N values after 180 days versus 33.8% observed for high quality milk (3.2 log cfu/mL, 0.42 U/mL).…”
Section: Resultsmentioning
confidence: 97%
“…The cold-active proteases from different microorganisms vary in their thermostability and alkalistability [41,43,73,65,63,101,105,129,130,131]. High proteolytic activity at lower temperatures shown by cold-active proteases is important in the commercial usage of proteases, but their low thermal stability is a common drawback that hinders their use in industries.…”
Section: Enhancing Thermo-stability Of Cold-active Proteasesmentioning
confidence: 99%
“…Furthermore, their presence is not only linked to undesirable alteration in appearance and flavour, but residual activity of bacteria proteases can be related to gelation of milk and coagulation of milk proteins as well (Harwalker et al. 1993;Tondo et al. 2004).…”
Section: Introductionmentioning
confidence: 99%